PENGARUH KOMPETENSI, MOTIVASI, DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BANDUNG BARAT - Lydia Novi Yanti (Jurnal Maps (Manajemen Perbankan Syariah), 2019)
This research is conducted in order to assess the effect of competency, motivation, and communication on employee’s performance (case studies at Dinas Pekerjaan Umum dan Penataan Ruang West Bandung Regency) partially and simultaneously. There are many factors that affect the employee’s performance, but this research is only limited to the factors of competency, motivation, and communication. The researcher used primary and secondary data. The research approach used is quantitative approach which the samples are 55 civil servants which is assessed by 5 Heads of Fields and 2 Heads Sub-Division. Before analyzing, all research validity and reliability instruments are examined. After the data are valid and reliable then analyzed by using classical assumption test, partial test (t test), and simultaneous test (F test) helping by IBM SPSS version 23 software. The result of analysis showed that competency, motivation, and communication variables are affected positively significantly and partially to the employee’s performance. Competency, motivation, and communication variables simultaneously affected positively and significantly about 54,3% and the rest is about 45,7% affected by other variable that is not observed in this research.